Formation of the Centre for Archaeological Heritage Protection in Ekaterinburg in the Late 19th — Early 20th Centuries - Andrey Vasilevich Shamanaev (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This article analyses the practical experience of the formation and functioning of regional public structures in the field of the cultural heritage protection in Russia in the late nineteenth — early twentieth centuries. The author focuses on the activity of the Ural Society of Natural Science Lovers (Ekaterinburg) and its special commissions (protection of archaeological and natural sites). The relevance of the study is due to the growing role of public organisations in cultural heritage protection. The works of the Ural Society of Natural Science Lovers provide valuable experience in organising a public initiative for the preservation of ancient heritage in regions that do not have a high concentration of scientific and higher education institutions. To analyse the material, the author uses procedural and historical-anthropological methods. The research refers to unpublished office documents (minutes of meetings, official correspondence) from the collection of the State Archive of Sverdlovsk Region and printed materials (minutes of meetings, reports) from Zapiski Ural’skogo Obshchestva Lyubiteley Yestestvoznaniya. An analysis of historiography and sources demonstrates that until the end of the nineteenth century, the main efforts of the Ural Society of Natural Science Lovers in the field of archaeological heritage protection of the Ural region were associated with the identification and museumification of such objects. The activities significantly changed in the 1890s–1910s. Specialised commissions were created within the structure of the society. They focused on the implementation of measures to preserve archaeological sites. At the same time, the Commission for the Protection of Natural Monuments paid considerable attention to the protection of natural objects with cultural layers (Kamennye Palatki in Shartash, etc.). An important condition for effective heritage protection was the interaction of the Ural Society of Natural History Lovers with state (central and local) and municipal bodies, and private individuals. A special relationship developed with the Imperial Archaeological Commission, which often directed the society’s activities in the field of cultural heritage protection.